Good Corporate Governance Principles in Indonesian Syariah Banking - Andrew Shandy Utama (International Journal of Law and Public Policy, 2020)
Sharia banks are banks that carry out their business activities based on the principles of Islamic law in banking activities based on fatwas issued by the National Sharia Council of the Majelis Ulama Indonesia. This research aims to explain the Good Corporate Governance principles in Indonesia sharia banking. The method used in this research is normative legal research. The results of the research explained that to maintain the trust of Indonesian people who are predominantly Muslim, sharia banking must apply the Good Corporate Governance principles in its management. The application of the Good Corporate Governance principles in sharia banking is strictly regulated in Article 34 Paragraph (1) of Law Number 21 of 2008, which emphasizes that sharia banks must implement good governance that includes the principles of transparency, accountability, responsibility, professionalism and fairness in carrying out its business activities. Form of application of the Good Corporate Governance principles in sharia banking is supervision conducted by the National Sharia Council of the Majelis Ulama Indonesia in general and the Sharia Supervisory Board specifically in each sharia bank.